Literary Criticism and Study of Navoi - Kuvanov Zarif Omonboevich (Research Parks Publishing LLC, 2021)
Literary criticism has achieved a lot of success in learning works of Alisher Navoi. The main and general part of great poet’s works consists of literary critical approaches to the art of literary words. It is important to note that, Alisher Navoi’s ideas about word art were formed under the influence of known critical attitudes of Uzbek, Arabic, Persian, and Azerbaijan nations, and those ideas improved due to his critical approaches to literature. “It is difficult to find such philosophes as Navoi in Persian literature, which could realize the specific features of great poets’ unique works and evaluate them appropriately.” Navoi investigated main theoretical basis of literature and art with literary critical approaches, tried to find solutions to main problems of literature, and paid much attention to the issue of social functions of literature. Navoi’s literary critical work has been studied in the works of A.Sadiy, A.Khayitmetov, B. Valikhujaev, X. Kudratullaev. During the period of Soviet literature the attitude towards classic literature was strict and it was pointed that “scientific- aesthetic, literary- critic ideas had not developed since the recolution”.